Genetic identity, epidemiology and management of faba bean (Vicia Faba L.) gall disease in Ethiopia - Bitew, B. (2022)
Ethiopia is the world’s second largest producer of faba bean (Vicia faba L.), and the crop has largest share of area and production of all pulses grown in Ethiopia. Faba bean is valued for its source of protein, income, and animal feedstock, and an important rotational crop. However, its current productivity is very low due to an emerging faba bean gall (FBG) disease and other biotic constraints. Initially, FBG disease-causing pathogen remained unconfirmed, but it was assumed to be caused by Olpidium sp. There also has been relatively a few data regarding the distribution of FBG, genetic identity of the pathogen, its damage on faba bean yield, reaction of genotypes and management methods in Ethiopia. Thus, the objectives of this study were to: (1) assess the distribution, disease intensity and host ranges of FBG; (2) determine the association of FBG intensity with major biophysical factors; (3) identify the genetic identity of FBG disease causal pathogen;(4) estimate yield losses caused by the disease; (5) evaluate phenotypic reactions of faba bean genotypes against the disease; (6) determine the stability of host resistance reactions to FBG disease under different agro-ecological conditions; and (7) develop an integrated FBG disease management options. In the FBG disease survey, a total of 783 faba bean fields were assessed across 14 districts (Bassona Worana, Ankober, Tarmaber, Asagert, Degem, Chole, Debay Telatgen, Sinan, Debark, Farta, Laygaint, Meket, Dessie Zuria and Enda Mehoni) and FBG disease prevalence and intensity, independent variables and alternate hosts were recorded. The associations of independent variables with disease incidence and severity were analyzed using logistic regression model. In the causative agent identification, crude DNA extraction and fixing on FTA cards and the morphological identifications were conducted at Debre Birhan Agricultural Research Center and International Livestock Research Institute (ILRI), Ethiopia. Molecular identifications were processed at Debre Birhan Agricultural Research Center (crude DNA extraction and fixing on FTA cards) and finally conducted at University of western Australia, Australia. The sequenced sample DNA were aligned using Geneious Prime version 2020.03 and then resulting consensus were BLAST in Genbank (NCBI). xv Yield loss assessment experiments were conducted on farmers’ fields at Bassona Worana using two moderately tolerant (Degaga and Gora) faba bean varieties and one susceptible local cultivar, two systemic fungicides [Bayleton 25 WP (Triadimefon 250 g kg-1), and Ridomil Gold MZ 68 WG (Metalaxyl 40+Mancozeb 640 g kg-1)] and two application schedules (10 and 15 days interval). The treatments were arranged in factorial combinations in a randomized complete block design (RCBD) with three replications. Faba bean gall severity, grain yield and yield-components for each treatment were collected and subjected to analysis of variance (ANOVA) using the PROC GLM procedure. Similarly, 415 faba bean genotypes, including four check varieties (Degaga, Gachena, Gora and local cultivar) were evaluated under natural field infections at farmers’ fields in augmented design with ten blocks at Bassona Worana during 2018 main cropping season. Among these 415 genotypes, 104 genotypes, which showed low FBG severity during 2018, were advanced in the 2019 cropping season for further evaluation using similar design and check varieties. Faba bean gall disease incidence, severity and grain yield data were collected and computed. Multi-location experiments were conducted in six locations at Bassona Worana, Debay Telatgen and Farta districts in the 2018 and 2019 main cropping seasons under natural infections using 21 faba bean genotypes arranged in a randomized complete block design with three replications. Disease incidence, severity and grain yield data were collected during the study periods. Additive main effect and multiplicative interaction (AMMI) and genotype and genotype x environment (GGE) biplot models were used to evaluate genotype stability reactions. Field-based integrated FBG disease management experiments were also conducted on farmers’ fields in Bassona Worana district during the 2018 and 2019 main cropping seasons. The treatments were three faba bean genotypes; two moderately tolerant faba bean genotypes (Degaga and Gora), and one susceptible local cultivar, two fungicides (Bayleton and Ridomil Gold) and two application schedules (10 and 15 days), which were arranged in a factorial combination in a randomized complete block design (RCBD) with three replications. Faba bean gall severity and grain yield data were collected and subjected to analysis of variance using the PROC GLM SAS procedure. The results of the survey revealed that FBG was found as a major production constraint in all the surveyed 14 districts considered with variable levels of incidence and severity. The highest (64%) mean FBG severity was recorded in Sinan district during 2018 and in Ankober (45%) during 2019. District, altitude (≥ 2700 m), poorly drained soil, high weed and crop density, flowering growth stage, manure xvi application, and early or late planting showed a highly significant (p 0.0001) association with high FBG incidence and severity. In the causal agent identification study, microscopic examination from infected faba bean leaves and stems confirmed an epibiotic phase of zoosporangia for dispersing zoospores, which are characteristic of Physoderma. The morphology did not show critical diagnostic characteristics of Olpidium viciae, such as presence of numerous short zoosporangial discharging tubes, or binucleate resting sporangia. Sequences derived from symptomatic tissue from partial ITS1-5.8S-partial ITS2, 18S-ITS1-5.8S-ITS2-part of 28S, and LSU (S28) all confirmed Physoderma and not Olpidium viciae, as the causal agent of FBG. The results of yield loss estimation study revealed that use of different faba bean varieties and applications of fungicides significantly (p0.05) reduced FBG epidemics and increased grain yield. In 2018, (62.5 and 54.1%), and in 2019 (42.2. and 45.1%), yield losses were calculated from unsprayed plots of variety Degaga and the local cultivar, respectively. Genotypes evaluation results showed that there were highly significant differences among the genotypes for FBG disease severity, AUDPC and grain yield as compared to check varieties. Low (37%) mean FBG severity and maximum (3.78 t ha-1) grain yield was recorded on faba bean accession number 1085. In the multi-location experiments, the AMMI and GGE biplot models analyses revealed highly significant (p0.001) variations among genotypes, environments and genotype x environment interactions (GEI) for FBG disease incidence. The genotypes contributed (80.32%) to the total variation observed far larger than the contributions from the environment (5.32%) and GEI (14.36%) for FBG incidence. Genotypes also showed larger (55.84%) contributions, followed by environment (37.83%) and GEI (6.33%) to the variability demonstrated for FBG severity. Similarly, the variation in grain yield was highly attributed to genotypes (50.86%), followed by environment (38.53%) and GEI (10.61%). Both in the AMMI and GGE biplot models analyses, G3, G16 and G17 showed low FBG severity, but less stable than the rest genotypes; and G7 showed low FBG severity and was stable. However, G1, G2, G5, G13, and G21 were susceptible at all test locations (Bassona Worana, Debay Telatgen and Farta districts) in main rainy seasons, in 2018 and 2019. The site Bassona Worana (E1) provided the best discriminating ability for the genotypes against FBG disease severity. On the other hand, G3, G4, G7, G16, and G17 produced high mean grain yield, but G8 gave high grain yield and was stable too. In developing IDM, integration of faba bean genotypes and fungicides significantly (p 0.05) reduced FBG disease epidemics and increased grain yield. The xvii variety Gora sprayed with Bayleton at a rate of 0.7 kg ha–1 and at 10-days interval had low mean FBG disease severity (21.67 and 10%), AUDPC value (1866.7 and 751.7%-days), low disease progress rate (0.0125 and 0.0121 units day-1) and high mean grain yield (3.70 and 5.03 t ha–1) in 2018 and 2019 main cropping seasons, respectively. Highest (3332.3%-days) AUDPC value was calculated from the unsprayed local cultivar in the 2018 main cropping season. Similarly, high marginal rates of return (7.16, 6.59 and 6.45) were recorded from the varieties Degaga, Gora and local sprayed Bayleton at 15 days interval in 2018. High marginal returns of 8.92 and 7.55 were obtained from the local cultivar and the variety Degaga in 2019 sprayed with Bayleton at 15 days interval. However, high marginal rate of return (8.85) was calculated from the variety Gora sprayed with Bayleton at 10 days interval in 2019. Generally, the findings of this study indicated that FBG is a major problem in faba bean production areas and the disease severity could be reduced by proper soil drainage; weed management, adjusting crop plant density, and following recommended planting time along with use of resistant/tolerant faba bean varieties. Symptomatology, morphological and molecular characterization confirmed that the causal agent of FBG disease is Physoderma. Integration of resistant/tolerant varieties and fungicide application reduces yield losses of faba bean due to FBG disease. Twenty-nine faba bean genotypes from the genotype evaluation experiment and four genotypes (G3, G7, G16 and G17) from multi-location experiments were identified for further evaluation and for the development of disease resistant/toleratn and high yielding varieties through crossing/breeding. Integration of moderately resistant/tolerant faba bean varieties (like Gora) with Bayleton fungicide, and spraying at the onset of the disease aligning at seedling, vegetative, flowering and podding growth stages are recommended to manage sustainably FBG disease and to increase faba bean grain yield at the study locations and other areas with similar agro-ecologies.